(untitled) (Global Journal of Medical Research, 2020)
A simple, specific, accurate and stability-indicating reversed phase high performance liquid chromatographic method was developed for the simultaneous determination of Rivaroxaban and Clopidogrel, using a C18 (25cm x 0.46 cm) Hypersil BDS column and a mobile phase composed of buffer (pH 4.5): methanol (70:30). The detection was carried out at wavelength 214 nm. The retention times of Rivaroxaban and Clopidogrel were found to be 3.300 min and 4.740min, respectively. Linearity was established for Rivaroxaban and Clopidogrel in the range of 2-6μg/ml and 7.5-22.5μg/ml, respectively. The percentage recoveries of Rivaroxaban and Clopidogrel were found to be 100.09% and 99.79%, respectively. Both the drugs were subjected to acid, alkali, oxidation, thermal and photolytic UV degradation. The degradation study shows that both drugs are susceptible in all parameter. Clopidogrel is more susceptible for photo and thermal degradation.